2010
DOI: 10.1177/0193945910386249
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Program to Reduce Depression

Abstract: Depression is increasing among Korean college students. Moreover, it is common for depressed individuals to consider attempting suicide. The purpose of this study therefore was to develop and examine the effectiveness of an intervention to reduce suicidal ideation and depression among female college students. Study participants were assigned to either an intervention (n = 27) or control (n = 31) group. The intervention group received a depression-reducing program in eight 1-hr weekly sessions. Measures of suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Cognitive behavioral intervention (CBI), which focuses on cognitive reconstruction and behavioral modification, has been widely recognized as an effective prevention and intervention approach for improving the mental health outcomes of university students. A large number of empirical studies have demonstrated that CBI can significantly decrease the social anxiety, depression and suicidal ideation, fear of public speaking, and psychological distress of university students with various mental disorders, especially in group settings (e.g., Bjornsson et al, 2011; Kim, Kim & Park, 2011; Monti, Tonetti & Bitti, 2014). Most importantly, recent studies have yielded promising outcomes on the preventive effects of CBI for various mental health problems, especially depression and anxiety.…”
Section: Mental Health Of University Studentsmentioning
confidence: 99%
“…Cognitive behavioral intervention (CBI), which focuses on cognitive reconstruction and behavioral modification, has been widely recognized as an effective prevention and intervention approach for improving the mental health outcomes of university students. A large number of empirical studies have demonstrated that CBI can significantly decrease the social anxiety, depression and suicidal ideation, fear of public speaking, and psychological distress of university students with various mental disorders, especially in group settings (e.g., Bjornsson et al, 2011; Kim, Kim & Park, 2011; Monti, Tonetti & Bitti, 2014). Most importantly, recent studies have yielded promising outcomes on the preventive effects of CBI for various mental health problems, especially depression and anxiety.…”
Section: Mental Health Of University Studentsmentioning
confidence: 99%
“…Algumas intervenções foram realizadas para diminuir não só a depressão, mas também a ansiedade e estresse. Essas intervenções foram feitas de forma virtual (Berry & York 2011;O'Hara et al, 2014) e por meio de encontros grupais, que envolveram técnicas de relaxamento, mindfulness e elementos da Terapia Cognitivo-Comportamental (Arredondo et al, 2015;Kim et al, 2010).…”
Section: Depressãounclassified
“…Os profissionais que estão na frente desse trabalho podem, com sua prática, promover ações de saúde e contribuir não apenas reduzindo sintomas, mas também promovendo ações de prevenção e promoção da saúde mental. Analisando o cenário internacional, verificam-se iniciativas bem-sucedidas de programas visando a promoção de saúde mental no ensino superior (Buchanan, 2013;Hintz et al, 2015;Kim et al, 2010;McCall et al, 2018;Nguyen-Feng et al, 2017). Esses trabalhos internacionais, cujas experiências foram profícuas, objetivaram desde a prevenção até a redução da sintomatologia de ansiedade, depressão e estresse em estudantes universitários.…”
Section: Considerações Finaisunclassified